Fishbone diagram: Application of root cause analysis in internal audit planning - Ardha, Novan Bastian Dwi; Riwajanti, Nur Indah; Haris, Zainal Abdul (Goodwood Publishing, 2023)
Purpose: This study applies a fishbone diagram to analyze the root cause of problems in the internal audit planning of J Corp, an Indonesian state-owned enterprise. Research methodology: A qualitative approach was employed to conduct a case study at the internal audit unit of an Indonesian state-owned enterprise. Research data were gathered from the results of focus group discussions with internal auditors, the analysis of the company’s standard operating procedure for internal auditing, and the observation of the workflow of internal audit planning. These data were then analyzed to identify the root causes of these problems. Results: Six key factors were identified that cause poor internal audit planning at J Corp. These are policies, processes, people, plants, programs, and products. To overcome these problems, this study provides several suggestions that can be implemented in the internal audit unit of J Corp. Limitations: This study is limited by the nature of the business and environment of J Corp, which affected the problems arising in the process of its internal audit planning; hence, the need to understand the entity to replicate this method for future research. Contribution: This study could be directly beneficial for internal auditors at J Corp to immediately improve the business process of internal audit planning. Furthermore, this study could contribute to future studies in which researchers or practitioners could replicate this method in another context. Novelty: The fishbone diagram was used to analyze the root causes of problems in the process of internal audit planning. Studies on the improvement of internal audit planning have been limited.